Different dietary assessment methods, similar conclusions? Comparison of a country's adherence to food-based dietary guidelines as depicted in two population-based surveys using different dietary assessment methods. Issue 9 (21st September 2022) - Karavasiloglou, Nena; Pestoni, Giulia; Dehler, Anna; Sych, Janice; Faeh, David; Rohrmann, Sabine
Abstract: Objective: Different methods of dietary intake assessment are frequently used to assess a population's diet. In this study, we aimed to compare the adherence to Swiss food-based dietary guidelines as depicted in two Swiss population-based surveys using different methods of dietary assessment. Design: Two population-based, cross-sectional surveys were compared. In the Swiss Health Survey (SHS), diet was assessed via a short set of questions on specific food groups, while in menuCH by two non-consecutive 24-h dietary recall interviews. Setting: To compare the diet depicted in these surveys, we used the Swiss food-based dietary guidelines on vegetable, fruit, dairy product, meat and meat product, fish and alcohol. The weighted proportion of responders meeting these guidelines was calculated for both surveys and was compared overall and by selected characteristics. Participants: Residents of Switzerland, selected from a stratified random sample of the non-institutionalised residents, who agreed to participate in the respective survey. To ensure comparability between the surveys, the age of the study populations was restricted to 18–75 years. Results: In menuCH, approximately 2 % of responders met ≥4 of the selected Swiss food-based dietary guidelines. In the SHS, using a cruder dietary assessment, the corresponding percentage was 20 %. In both surveys, more women and never smokers were meeting ≥4 food-based dietary guidelines compared to men and current or former smokers, respectively. Conclusions: Our study comparing the diet in two population-based, representative surveys detected large variations in guideline adherence depending on the dietary assessment method used.